Hubungan Akal Dan Wahyu Menurut Teolog Muslim - Yudi Kuswandi (STAI Siliwangi Bandung, 2015)
Tersetting sense to describe the nature of truth. He can tell the difference deeds good and bad, love and hate, lies and truth, falsehood and of truth. In human nature also has drawbacks, such as weakness in abstinence so gullible power, like a hasty, inaccurate, and so forth. Then this is where the urgency of Revelation is guiding sense to the truth, because people will not know the true nature except berpondasi on revelation. IbnTaymiyya and IbnHazm's position as an instrument Intellect condition or disposition